2023
DOI: 10.3390/agriculture13081548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altitude and Continuous Cropping on Arbuscular Mycorrhizal Fungi Community in Siraitia grosvenorii Rhizosphere

Abstract: Siraitia grosvenorii, a medicinal plant with continuous cropping, is cultivated in southern China. Changes in the soil microbial community during continuous cropping can cause soil-borne diseases in S. grosvenorii. This experimental study aimed to determine the differences in the arbuscular mycorrhizal fungi (AMF) community structure and root colonization in the rhizosphere soil of S. grosvenorii with different continuous cropping years and altitudes. We tested three altitude gradients (low, 200–300 m; middle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…These advantages may be attributed to the positive feedback loop between AMF and acidic soil stress. This understanding aligns with the results of a study that evaluated the pH of Siraitia grosvenorii in Guangxi; in this study, an increase in AMF richness and diversity was observed with increasing pH [25]. Therefore, exploring the sensitivity of mycorrhizal fungi to soil pH and evaluating how soil pH drives microbial niche differentiation in rocky desertification areas could offer innovative approaches to harness biodiversity for the mitigation of rocky desertification and facilitation of ecological restoration.…”
Section: The Relationship Between Amf Community and Soil Characteristicssupporting
confidence: 86%
See 3 more Smart Citations
“…These advantages may be attributed to the positive feedback loop between AMF and acidic soil stress. This understanding aligns with the results of a study that evaluated the pH of Siraitia grosvenorii in Guangxi; in this study, an increase in AMF richness and diversity was observed with increasing pH [25]. Therefore, exploring the sensitivity of mycorrhizal fungi to soil pH and evaluating how soil pH drives microbial niche differentiation in rocky desertification areas could offer innovative approaches to harness biodiversity for the mitigation of rocky desertification and facilitation of ecological restoration.…”
Section: The Relationship Between Amf Community and Soil Characteristicssupporting
confidence: 86%
“…This study revealed the AMF germplasm resources in the rhizosphere of S. japonica, and 22 species were identified by Glomus. Glomus has also been identified as a predominant genus in the rhizosphere of other medicinal plants, including Rosa laevigata Michx [24] and Siraitia grosvenorii [25]. These results may, ultimately, be attributed to the adaptive characteristics of Glomus.…”
Section: Characteristics Of the Amf Community In The Rhizosphere Of S...mentioning
confidence: 99%
See 2 more Smart Citations
“…The RawReads data at both ends were subjected to individual quality clipping using the Fastp software (version 0.14.4), while the primers at both ends were eliminated through the employment of the Cutadapt software (version 1.14), thereby yielding valid sequences [39]. Subsequently, the Usearch software's Uparse (version 10.0.240) algorithm was employed to cluster the sample quality sequences into OTUs, and the Silva 16S database was utilized to annotate the species, thereby obtaining taxonomic information for the OTUs.…”
Section: Bioinformatic Analysismentioning
confidence: 99%